Mitosporic fungi associated with native Nothofagus trees from the Andean-Patagonian Forests of Argentina - Sanchez, Romina Magali (2014)
The Andean Patagonian Forest is one of the most unique biogeographic formations of Argentina. It is characterized by cold temperate forests with several endemic tree species and is also considered an important reservoir of a large number of yet unknown fungal species. Therefore, as a contribution to the knowledge of the ascomycetes of Argentina, which are poorly known, a study was performed to identify saprophytic fungi associated with bark and woody debris. This survey included samples from five out of the six species of native Nothofagus trees present in the Andean Patagonian forest of Argentina. These are historically related to the Nothofagus trees from Australia and New Zealand. Microfungal records from these Australasian trees are high and similar numbers were expected to occur on those in South America. A review of the fungal records of both continents shows a predominance of mitosporic species on Nothofagus trees. Moreover, eleven anamorphic species were found and are presented here for the first time. Among them five are described as new (Dictyosporium dewiñi nom. prov., Endomelanconium macrospora nom. prov., Petrakia reticulate nom. prov., Pseudochuppia tuberculata nom. prov. and Trimmatostroma ornata nom. prov.), four genera (Acarosporium, Dwiroopa, Petrakia and Pseudochuppia) and one species (Monodictys paradoxa) are recorded for the first time in South America and two species (Bactrodesmium atrum and Gilmaniella multiporosa) are recorded for the first time in Argentina. When comparing the fungal species present on Nothofagus trees in both continents it appears that there are few in common. The same happens when comparing those in neighboring countries (Argentina and Chile). This suggests that environmental conditions may have a greater influence than substrate conditions on the diversity of ascomycetes species.